New Study of Mgo Nps in Drilling Fluid to Reduce Stick-Slip Vibration in Drilling System - Y. Alssafar, Saifalden; H. M. Al-Mahdawi, Faleh (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Stick-slip is kind of vibration which associated with drilling operation in around the bottom hole assembly (BHA) due to the small clearance between drill string & the open hole and due to the eccentric rotating of string. This research presents results of specific experimental study that was run by using two types of drilling mud (Fresh water Bentonite & Polymer), with/without Nanoparticle size materials of MgO in various ratios and computes the rheological properties of mud for each concentration [Yield point, plastic viscosity, Av, PH, filter loss (30 min), filter cake, Mud Cake Friction, Friction Factor]. These results then were used to find a clear effects of Nanoparticle drilling mud rheology on stick - slip strength by several perspectives through a special “Torque and Drag” software which simulate the torque amount expected on BHA during drilling a vertical well in different conditions using real drilling string design that usually used in Iraqi oil fields. Thus to mitigate or to prevent stick–slip and cure the sequence events that could happen to both of drilling string and the well, i.e. Bit/BHA wear, pipe sticking, borehole instability and low Rate of penetration. Our study concluded that there are good reduction in the torque from (2031lb-ft) to (1823lb-ft) using polymer mud and torque reduction from (4000lb-ft) to (3450lb-ft) using Fresh Water Bentonite, these results do not include any breaking in the satisfactory range of other mud rheology.